Quantitative study on the role of supersaturation during sublimation growth on the yield of 50 mm diameter 3C-SiC - Rankl, Dominik; Jokubavicius, Valdas; Syväjärvi, Mikael; Wellmann, Peter (Materials Science Forum, 2015)
We have investigated the crystal growth of 3C-SiC using physical vapor transport growth in the temperature range from 1800°C to 1950°C. The supersaturation was determined using numerical modeling of the temperature field and gas phase composition by applying quasiequilibrium thermodynamic conditions. Analysis of the 3C-SiC yield was carried out by optical microscopy, optical absorption, Raman spectroscopy and x-ray analysis. Quantitative data on supersaturation are compared with most stable 3C-SiC nucleation and growth condition. Our interest is in particular to understand how to use sublimation epitaxy experience in 3C-SiC growth to a PVT set up that could open up the possibility of large area bulk growth. As indicative measure, the application to large area growth in a physical vapor transport growth reactor is briefly addresse
Keywords: Cubic SiC; Bulk growth; Sublimation Growth; Supersaturation